Caracterização da diversidade bacteriana e sensibilidade antimicrobiana de bactérias isoladas de morcegos da região metropolitana de Fortaleza - Nobre, Juliana Araújo (2023)
Bats are flying mammals notably known as natural reservoirs of several potentially zoonotic pathogens, such as viruses, bacteria, fungi and protozoa. However, studies on the microbiota of bats, including in the northeast region of Brazil, are scarce. Thus, the objective of this work was to isolate and identify bacteria from bats in the Metropolitan Region of Fortaleza (MRF), Ceará, and to evaluate them for antimicrobial susceptibility. A total of 51 bats, of nine species, four genus, and six different feeding habits, were captured in three municipalities (Pacatuba, Itaitinga and Maranguape), where they sheltered in abandoned or little-used buildings, in 2021 and 2022. Samples of swabs (oropharynx and rectum) and guano were obtained, totaling 117 samples, 101 of which were swabs and 16 were guano. In the laboratory, the samples were cultivated in MacConkey agar and blood agar 5% with Columbia base. After screening and stock, the isolates were submitted to biochemical identification. Antimicrobial susceptibility tests were performed, using the disk-diffusion or microdilution method. A total of 222 bacteria were obtained, with 135 Gram-negative bacilli (GNB), 63 Gram-positive cocci (CGP) and 24 Gram-positive bacilli (BGP). Bacteria of the order Enterobacterales (especially the genus Enterobacter, Klebsiella and Escherichia) and Staphylococcus coagulase negative (S. xylosus and S. sciuri) were the most common. Resistance to at least one antimicrobial was observed in 59.8% (113/189) of the isolates, in 80.4% (41/51) of the animals, and in 100% of the guano samples tested. Of these, the species D. rotundus and guano from mixed species colonies (P=0.0026) stood out. The antimicrobials to which, BGN and CGP, showed the most resistance were cephalothin and ampicillin (P<0.0001). The present study presents unprecedented data on the characterization of bacterial diversity and antimicrobial sensitivity of bacteria from the gastrointestinal tract (GIT) of bats from the RMF. Considering that these wild animals were never treated with antimicrobials, the origin of the high resistance to antimicrobials observed is questioned, and research is needed from the One Health approach to better understand the dynamics of resistance acquisition of bacteria from TGI microbiota of bats.